BOLOGNA PROCESS: EVOLUTION OF PRIORITIES AND INTERIM RESULTS - Gennady F. Tkach; Vasily S. Senashenko (Высшее образование в России)
The article discusses the evolution of the educational and social priorities during the Bologna principles implementation. The authors analyze interim results of the European Higher Education Area formation and the outcomes of the transformation of educational systems of the countries participating in the Bologna process.